Aplicação de catalisadores híbridos magnéticos no processo eletro-Fenton heterogêneo para degradação de compostos orgânicos em amostras reais - Cruz, Daiane Requião de Souza (2022)
Advanced electrochemical oxidative processes (AEOP) stand out as promising technologies and alternatives to conventional techniques in the degradation of numerous polluting substances discarded in water bodies. This thesis proposes the application of AEOP, electrochemical oxidation with electrogenerated hydrogen peroxide (OE-H2O2) and the heterogeneous electro-Fenton (EF) process with new magnetic hybrid catalysts to treat contaminated water. The electrochemical system was equipped with a boron-doped diamond anode (DDB) and the cathode with a gas diffusion electrode (GDS) for the electrogeneration of H2O2. The results obtained are presented in two chapters. In Chapter 1, the catalytic efficiency of the cobalt ferrite hybrid synthesized using natural organic matter (MON) as an organic precursor, calcined at 200 °C (Hb200) was evaluated on the degradation and mineralization of the Acid Black 210 dye in synthetic solution and in leather tanning effluent. In the synthetic solution, the electrochemical tests occurred at pH 3, current density 28 mA cm-2, varying the catalyst mass and dye concentration. The best conditions achieved were 30 mg of Hb200 and 55 mg L-1 of the dye. These conditions were applied in the effluent treatment at pH 3 and 6 (without adjustment) and the superiority of EF-Hb200 (97.4% TOC) was verified in relation to OE-H2O2 (85.5% TOC). The catalytic response in the removal of TOC was similar at both pH values (95.3%-pH 3 and 97.4%-pH 6), thus, the catalyst was reused at pH 6 and at the end of three treatment cycles ( 7 h), showed only a 10% drop in efficiency. The analysis by gas chromatography and mass spectrometry proved the effectiveness of EFHb200 by the drastic reduction of degradation products before and after the effluent mineralization process. In Chapter 2, the removal of MON in natural water matrices was studied to minimize the by-products formed during the disinfection of water with chlorine. Cobalt ferrite (HbCo), manganese ferrite (HbMn), magnetite (HbFe) and cobalt ferrite catalysts with iron precursors from mining residues (HbSF and HbLM) were synthesized via the modified sol-gel route, characterized by X-ray and infrared, by which the required ferrite phases were confirmed. The optimal mineralization condition of MON using HbCo was pH 3, current density 28 mA cm-2 and 15 mg of catalyst. Under these conditions, HbLM showed a greater catalytic response at the end of 7 h of treatment, and the other hybrids showed similar efficiencies. As it presents less leaching of metallic ions, HbCo was used in the EF process to treat different natural water matrices. The results showed that EF-HbCo promoted high MON removal rates (82-91%) in river waters containing both hydrophobic and hydrophilic MON fractions. Thus, the catalysts studied in this work through the electro-Fenton process proved to be effective in removing the organic load from real matrices with a high degree of complexity